2006
DOI: 10.1111/j.1467-8306.2006.00704.x
|View full text |Cite
|
Sign up to set email alerts
|

Land Reform, Range Ecology, and Carrying Capacities in Namaqualand, South Africa

Abstract: In South African rangeland management, there is a long history of using the notion of carrying capacity as a central planning tool for environmental conservation and agricultural modernization. Today, in the new South Africa, the ''need'' for livestock keepers to adhere to a defined carrying capacity in order to conserve rangeland resources and to achieve economic development remains an institutionalized ''fact.'' In this article, we use interviews, livestock and rainfall data, policy documents, and aerial pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
75
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 32 publications
(34 reference statements)
1
75
0
1
Order By: Relevance
“…Community-based adaptation initiatives are increasing in response to the top-down, technical approaches promoted by the scientific discourse on climate change (Huq and Reid, 2007). In the dominant scientific discourse, practices of the poor have often been blamed for environmental degradation, and resource control has consequently been transferred from local populations to central governments or to private actors (Benjaminsen et al, 2006). The third principle of sustainable adaptation recognizes that successful responses involve integrating local knowledge with other sources of knowledge about climate change.…”
Section: Key Principle 3: Integrate Local Knowledge Into Adaptation Rmentioning
confidence: 99%
“…Community-based adaptation initiatives are increasing in response to the top-down, technical approaches promoted by the scientific discourse on climate change (Huq and Reid, 2007). In the dominant scientific discourse, practices of the poor have often been blamed for environmental degradation, and resource control has consequently been transferred from local populations to central governments or to private actors (Benjaminsen et al, 2006). The third principle of sustainable adaptation recognizes that successful responses involve integrating local knowledge with other sources of knowledge about climate change.…”
Section: Key Principle 3: Integrate Local Knowledge Into Adaptation Rmentioning
confidence: 99%
“…10 The Succulent Karoo biome, including the Namaqualand region, is globally recognised as a biodiversity hotpot that is particularly vulnerable to climate change, 11 not only because of the high levels of biodiversity but also because of a high dependence of the region's population on natural resources, livestock production, and dryland agriculture. 12,13 Modelling studies have indicated that the Succulent Karoo may suffer a reduction in spatial extent of up to 40% as well as consequent reductions in the abundance and diversity of endemic species as a result of changes in temperature and rainfall. 14,15 In terms of individual species' responses to climate change, a study by Broennimann et al 16 found that geophytes and succulents, which make up over half of plant species in Namaqualand, were particularly vulnerable to climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Turner 1993;Bassett & Koli Bi 2000;Benjaminsen et al 2006;. While researchers and policymakers have been 'misreading African landscapes' (Fairhead & Leach 1996), we ask whether there is ground for a parallel shift in thinking about the Arctic.…”
Section: Introductionmentioning
confidence: 99%